A139 EQUITY IN ACCESS TO COLORECTAL CANCER SCREENING IN NOVA SCOTIA. (21st February 2022) - Sullivan, R; Jones, J; Williams, C; Kilfoil, E; MacIntosh, D; Stewart, M J
Abstract: Background: Population-based colorectal cancer (CRC) screening programs aim to minimize inequities in participation through universal access, however, there remain disparities associated with low education, socio-economic status, and population centre. In the United States racialized groups have lower screening participation, and Black and Indigenous adults have higher CRC mortality. There is no Canadian data on racialized group participation in CRC screening because racial and ethnic data is not routinely collected. The Nova Scotia Colon Cancer Prevention Program (NSCCPP) mails fecal immunochemical tests (FIT) biennially to all residents aged 50–74 and allows for optional self-identified race and ethnicity. Aims: To determine whether participation rates in the NSCCPP differ on the basis of race/ethnicity, age, sex, or population centre. In this preliminary analysis we report screening participation on the basis of race/ethnicity. Methods: A retrospective cohort study was performed using the NSCCPP database to identify screen-eligible adults who returned a FIT to the program (i.e. participated) from 2011 to 2021. Racialized groups were identified based on self-identification form results allowing for multiple category selections. Race/Ethnicity was categorized as White, Black/African Canadian, Indigenous, Asian, Middle Eastern. The 2016 Canadian census was used to estimate the screen-eligible population (age 50–74) and race/ethnicity group population sizes. Unique participants were identified as individuals who returned one or more FITs in the study period. Unique participants were compared to the screen-eligible population to estimate participation over the 10-year study period. Results: 508, 533 FITs were returned over 10 years by 208, 702 unique participants. The number of annual FITs returned ranged from 14, 066 in 2011 to 65, 746 in 2019. Participants were 56% female, 44% male, with a mean age 62.8 (± 7.0). FIT status was 89% negative, 7% positive, and 4% indeterminate. 96% (n=490, 398) of participants provided self-identification data. Table 1 provides the screen-eligible population, unique participants, and FIT participation over the 10-year study period all characterized by race/ethnicity. Over 10 years, 59% of the eligible population participated in CRC screening by returning at least one FIT. Conclusions: CRC screening participation by race/ethnicity in Canada is unknown. This analysis of the NSCCPP suggests that participation by racialized individuals including Black/African Canadian, Asian, and Indigenous, are lower relative to White individuals. Further analyses will explore race/ethnicity and gender in terms of temporal and geographic trends. Table 1. Funding Agencies: None